Identification Attitudes of Learners on Physics Subjects - Dwi Agus Kurniawan; astalini astalini; Rahmat Perdana; Wawan Kurniawan (Universitas Negeri Makassar, 2019)
This study aims to determine the attitudes of students in physics learning at the State High School in Batanghari Regency. The type of research used is quantitative which uses a research design survey that is strengthened by the results of interviews to support the results of quantitative data. This study involved 926 students of the Batanghari State High School. The data used by researchers in the form of a questionnaire/questionnaire consisting of 54 item statements using a Likert scale 5. Quantitative data analysis using descriptive statistics. The results of this study the researchers get the results of Good and Good Enough with the following details: The Social Implications of Physics have a Good result, amounting to 51.3%. Attitudes in Physics Investigation have a sufficient result of 44.3%, Enjoyment Learning Physics has Enough results of 55.5%, Career Interest in Physics has Enough result of 45%. This is due to the attitude that is sufficient on the indicator. The adequate attitude of students is a balanced attitude in learning Physics Subjects because subjects are difficult to understand.